Implementation of School Self-Evaluation in Improving Education Equality at SD Negeri 1 Kebonharjo - Emi Lutfia; Aniq Jihan Furoidah; Akhmad Sodiq; Eka Wulandari; Ngurah Ayu Nyoman (Tadrib: Jurnal Pendidikan Agama Islam, 2025)
This study examines the implementation of School Self-Evaluation (SSE) as a strategic initiative to improve educational quality at SD Negeri 1 Kebonharjo, Kendal Regency. Employing a qualitative descriptive approach, data were collected through interviews, observations, and document analysis involving school stakeholders, including the principal, teachers, and school committee members. The findings indicate that the school has initiated a structured SSE process, beginning with data collection and needs analysis, which has led to the formulation of follow-up improvement plans. SSE has been instrumental in identifying institutional strengths and weaknesses, serving as a foundation for targeted quality improvement programs aligned with national education standards. The principal plays a pivotal role in facilitating the evaluation process, conducting academic supervision, and promoting a culture of continuous improvement. Despite these efforts, the study highlights challenges such as limited parental and committee engagement, as well as the pressures of external accountability. The research highlights the importance of stakeholder capacity-building and the need for enhanced collaboration among school stakeholders to ensure sustainability and impact. This study contributes to the growing body of literature on internal quality assurance mechanisms in primary education, offering practical insights for schools seeking to institutionalize self-evaluation as part of their development strategy